Ensuring Redd+ Safeguards For Socioeconomic Sustainability Of Forest Dependent Mountain Communities (A Case Study Of Private Forests Of Gilgit Baltistan, Pakistan) - Hussain, Kamran (2013)
Pakistan has joined UN-REDD program and started REDD+ initiatives in 2010. Darel and Tangir valleys in Gilgit Baltistan have been selected as one of the potential sites identified for REDD+ demonstration in the country. However, the implementation of REDD+ seems challenging as the forests in Darel and Tangir are owned by communities and their important livelihoods are dependent on these forests. The efficient pre-planning, therefore, requires special focus on social and economic safeguards. The main purpose of this study was to identify the potential REDD+ safeguards associated with livelihoods, forest land tenure and access rights and the local community participation in the private forests located in dry temperate mountain areas. The objectives of this study were (i) to assess the current forest resource based livelihoods and their relationship with the overall well being status of the mountain communities living in private forests (ii) to explore the current forest land tenure systems and access rights of the dependent communities and (iii) to identify the potential safeguards related to livelihoods, land tenure and access rights as well as community participation. The areas selected for this study were private forests of Darel and Tangir Valleys situated in the Northern Province i.e. Gilgit-Baltistan of Pakistan. A Case study approach was adopted for this study and a total of 128 households were randomly selected from ten village of both the valleys targeted at three groups i.e. religious leaders, members of village organization and local community. The data was analyzed by using simple descriptive statistics.